2006
DOI: 10.1002/dvdy.20999
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression and localization of serine protease HtrA1 in human endometrium and first‐trimester placenta

Abstract: Mammalian embryos cannot survive without the placenta. Development of the human placenta requires trophoblast proliferation, differentiation, and invasion as well as highly coordinated modulation of the maternal uterus. HtrA1 is a member of the recently identified mammalian HtrA (high temperature requirement factor A) serine protease family with a high level of expression in the placenta. In this study, we examined whether HtrA1 expression (mRNA and protein) is associated with placental development in the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…The mRNA expression profile (cluster 6) was similar to those of fibrillar collagens. In addition, the expression of HTRA1 has been shown in the human placenta at the maternal-trophoblast interface (Nie et al 2006). The mRNA expression profiles of all these genes suggest a complex regulation of the ECM remodelling in the bovine endometrium during the oestrous cycle.…”
Section: Discussionmentioning
confidence: 98%
“…The mRNA expression profile (cluster 6) was similar to those of fibrillar collagens. In addition, the expression of HTRA1 has been shown in the human placenta at the maternal-trophoblast interface (Nie et al 2006). The mRNA expression profiles of all these genes suggest a complex regulation of the ECM remodelling in the bovine endometrium during the oestrous cycle.…”
Section: Discussionmentioning
confidence: 98%
“…HTRA1 mutations also cause the genetic vascular disease, cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL; Hara et al., 2009). The protein is implicated as a tumor suppressor and shown to play an important role in extracellular matrix remodeling during placental development and arthritis (Chien et al., 2004; Grau et al., 2006; Nie et al., 2006). It cleaves and inhibits TGF beta, and several extracellular matrix proteins, including fibronectin and amyloid precursor protein (Beaufort et al., 2014; Grau et al., 2005; Oka et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The highest expression was detected in mature layers of epidermis (De Luca et al, 2003). It was demonstrated that HTRA1 expression in glandular and stromal cells increases gradually across menstrual cycle and reaches the maximum level at the mid-and late secretory phases (Nie et al, 2006). It was also reported that HTRA1 expression changes during pregnancy both in placental and endometrial cells.…”
Section: Expressionmentioning
confidence: 94%
“…It was also reported that HTRA1 expression changes during pregnancy both in placental and endometrial cells. Upregulation of HTRA1 was observed in endometrial glands and decidual cells during preparation of endometrium for embryo implantation and during the first trimester of placentation (Nie et al, 2006). However, the highest expression of HTRA1 was detected in placenta in the third trimester of gestation (De Luca et al, 2004).…”
Section: Expressionmentioning
confidence: 97%